Ultrasound evaluation of pouch of Douglas obliteration and rectal deep endometriosis in women who have had previous combined colorectal and gynaecological laparoscopic surgery for rectal endometriosis: A pilot study. (9th January 2020) - Alhayo, Sam; Leonardi, Mathew; Lu, Chuan; Gosal, Preet; Reid, Shannon; Barto, Walid; Condous, George
Abstract : Background: Ultrasound has been demonstrated to accurately diagnose rectal deep endometriosis (DE) and pouch of Douglas (POD) obliteration. The role of ultrasound in the assessment of patients who have undergone surgery for rectal DE and POD obliteration has not been evaluated. Aim: To describe the transvaginal ultrasound (TVS) findings of patients who have undergone rectal surgery for DE. Materials and Methods: An observational cross‐sectional study at a tertiary care centre in Sydney, Australia between January and April 2017. Patients previously treated for rectal DE (low anterior resection vs rectal shaving/disc excision) were recruited and asked to complete a questionnaire on their current symptoms. On TVS, POD state and rectal DE were assessed. Correlating recurrence of POD obliteration and/or rectal DE to surgery type and symptoms was done. Results: Fifty‐six patients were contacted; 22/56 (39.3%) attended for the study visit. Average interval of surgery to study visit was 52.8 ± 24.6 months. Surgery type breakdown was as follows: low anterior resection (56%) and rectal shaving/disc excision (44%). The prevalence of POD obliteration was 16/22 (72.7%) intraoperatively and 8/22 (36.4%) at study visit, as per the sliding sign. Nine patients (39.1%) had evidence on TVS of recurrent rectal DE. Recurrence of POD obliteration and rectal DE was not associated with surgery type or symptomatology. Conclusion: Despite surgery for rectal DE, many patients have a negative sliding sign on TVS, representing POD obliteration, and rectal DE. Our numbers are too small to correlate with the surgery type or their current symptoms.